Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan - Muhamad Ekhsan (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2019)
This study aims to examine and analyze the effect of motivation and work discipline on the performance of PT Syncrum Logistics Employees. Data collection is done by distributing questionnaires with a total sample of 60 respondents and using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis in the form of multiple linier regression tests. The results of this study indicate that partially and simultaneously variable motivation and discipline affect the performance of PT Syncrum Logistics employees. This is evidenced from the results of the simultaneous test ( F Test) and the result of the Partial Test (t Test) also showing significant values of the two independent variables that support the hypothesis. Therefore the test result from this study state that there is a simultaneous influence between the variables of motivation and work discipline on the performance of the PT Syncrum Logistics Keywords: motivation, discipline, performance